Encountering Islam and Local Culture in Massorong Tradition in the Mandar Bay - Sumarni, Sumarni; kaco, Suardi; Sumarni; Suardi Kaco (JURNAL JAWI, 2024)
This research delves into the encounter between Islam and local culture within the community of Teluk Mandar. Utilizing phenomenological, historical, and cultural anthropology approaches, the findings unveil that initially, the encounter was peaceful, yet encountered resistance from certain residents post their Islamic studies at the local boarding school, citing the tradition as contradictory to Islamic teachings. Nevertheless, the tradition perseveres as a means to uphold environmental equilibrium and foster a tranquil and prosperous life. Traditional figures retain their pivotal roles, with Islamic elements seamlessly integrated into the ritual. In summary, the encounter between Islam and local culture within the Massorong tradition reflects mutual influence, accommodation, and potential conflict, necessitating profound comprehension and dialogue to sustain community harmony.